FORMATION OF INDEPENDENT THINKING OF STUDENTS - Sharipova Maftunaxon Shavkat qizi; Baydjanova Iroda Abdullayevna (Web of Journals Publishing, 2025)
The modern system of higher education should be considered as the most important institution of socialization of the individual, in which training and education is a single process aimed at training highly educated, widely erudite, cultural, creative thinking specialists.
Keywords: Independent thinking, non – traditional method, innovation, education, lesson.